2018 IEEE International Conference on Robotics and Automation (ICRA) 2018
DOI: 10.1109/icra.2018.8462925
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Incremental Boltzmann Machine for Modeling Context in Robots

Abstract: Context is an essential capability for robots that are to be as adaptive as possible in challenging environments. Although there are many context modeling efforts, they assume a fixed structure and number of contexts. In this paper, we propose an incremental deep model that extends Restricted Boltzmann Machines. Our model gets one scene at a time, and gradually extends the contextual model when necessary, either by adding a new context or a new context layer to form a hierarchy. We show on a scene classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…We also analyzed how the system behaves when a new context is added, as shown in Figure 5. Here, comparing with the result of Celikkanat et al [4] and Dogan et al [22] (iRBM and diBM models), we see that our system converges to the correct number of contexts and yields the same level of entropy for the system, where entropy is defined as follows (as in [4]):…”
Section: B Applying Cinet To Incremental Context Modelingsupporting
confidence: 75%
See 1 more Smart Citation
“…We also analyzed how the system behaves when a new context is added, as shown in Figure 5. Here, comparing with the result of Celikkanat et al [4] and Dogan et al [22] (iRBM and diBM models), we see that our system converges to the correct number of contexts and yields the same level of entropy for the system, where entropy is defined as follows (as in [4]):…”
Section: B Applying Cinet To Incremental Context Modelingsupporting
confidence: 75%
“…On an artificial dataset and a real dataset (SUN-RGBD scene dataset [21], we show that the network learns to add a new context when it decides necessary on encountering new scenes. Moreover, we compared our method with another incremental Latent Dirichlet Allocation method [4] and incremental Boltzmann Machines [22], and demonstrated that it performs better.…”
Section: B Contributionsmentioning
confidence: 99%
“…These include deep Boltzmann machine 103,104,140 and DBNs. Dogan et al 105 presented an incremental and hierarchical model for task-related context modeling in robotics using RBM to model service robot’s context incrementally and achieved competitive performance compared with other techniques.…”
Section: Deep Neural Networkmentioning
confidence: 99%
“…However, in real settings, the set of objects can grow in time. To overcome this problem, the input layer should be designed in an incremental manner, as suggested in [17,65,66].…”
Section: Limitations and Future Workmentioning
confidence: 99%